Comparative analysis of the dynamics of heart rhythm variability indicators of long-distance runners in different training conditions - Bakayev, V.; Bolotin, A. (SportMont, 2019)
It has been established that the dynamics of rest/load indicators, as a rule, depends on the skill level of the athlete. More successful athletes have a high level of sympathetic reaction and activity of the central circuit for the regulation of heart rhythm to the load as a manifestation of functional reserves mobilization. A healthy powerful reaction to load and a high level of mobilization abilities are the most important parameters for the success of training and competitive activities during race running. The findings of a comprehensive assessment of heart rate variability in the evaluation of short 5-minute records and long (weekly) records indicate that, compared with athletes who train at the medium altitude, long-distance runners training on the flat terrain adapt to the conditions of sports activity with higher strain on regulatory systems. This is due to the lack of proper economization against the background of the initially low reserve and aerobic capabilities of the body, due, inter alia, to the low development of the autonomous control circuit. The above leads to overload and depreciation of the central control circuit at rest and, in connection with this, its low response to the impact under the conditions of physical and competitive loads. The cost of adaptation of such an organism increases significantly, its adaptation and competitive potential decreases. Accordingly, with a highly developed autonomous control circuit during training at the medium altitude, we can expect a higher competitive success of the long-distance runners compared to the long-distance runners who train on the flat terrain with poorly expressed control circuit.